Teoria para una praxis. Splendor "realitatis" - Argelés, Teresa; Bonet, Adelina; Clemente, Ignacio; Estévez, Jordi; Gibaja, Juan; Lumbreras, Luis G.; Piqué, Raquel; Ríos, Marcela; Taulé, María Angela; Terradas, Xavier; Vila, Assumpció; Wünsch, Germà (Trabalhos de Antropologia e Etnologia, 2020)
.